(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the current context of strategic economy, economic and statistical analysis of the economy of the country, especially its regions, is very important. Examples of this are the Decree of the President of the Republic of Uzbekistan PF-4947 of February 7, 2017 "On the Strategy of actions for the further development of the Republic of Uzbekistan" and August 8, 2017 "On measures to accelerate the socio-economic development of the regions." Resolutions No. 3182 specify the issues aimed at the complex, balanced, socio-economic and investment and innovative development of regions, districts and cities as a priority.